Prevalence of Drug Resistance-Associated Gene Mutations in Plasmodium vivax in Central China - Lu, Feng (The Korean Society for Parasitology and Tropical Medicine, 2012)
Resistance of Plasmodium spp. to anti-malarial drugs is the primary obstacle in the fight against malaria, and molecular markers for the drug resistance have been applied as an adjunct in the surveillance of the resistance. In this study, we investigated the prevalence of mutations in pvmdr1, pvcrt-o, pvdhfr, and pvdhps genes in temperate-zone P. vivax parasites from central China. A total of 26 isolates were selected, including 8 which were previously shown to have a lower susceptibility to chloroquine in vitro. For pvmdr1, pvcrt-o, and pvdhps genes, no resistance-conferring mutations were discovered. However, a highly prevalent (69.2%), single-point mutation (S117N) was found in pvdhfr gene. In addition, tandem repeat polymorphisms existed in pvdhfr and pvdhps genes, which warranted further studies in relation to the parasite resistance to antifolate drugs. The study further suggests that P. vivax populations in central China may still be relatively susceptible to chloroquine and sulfadoxine-pyrimethamine.